Balloon Entrapment: An Unusual Complication of Detachable Balloon Embolization of Traumatic Caroticocavernous Fistula - Santhosh Kumar Kannath; Jayadevan Enakshy Rajan (Journal of Clinical Interventional Radiology ISVIR)
Traumatic caroticocavernous fistula was attempted to embolize using detachable balloons. Though the fistula could be occluded, unexpected complication was observed during the detachment of the balloon, and the fistula was later tackled using coils and liquid embolic agent. Failure analysis revealed an interesting correlation between the anatomy of sac and the course of the balloon mounted microcatheter.